Trophic control of cryptic coralline algal diversity - Hind, Katharine R.; Starko, Samuel; Burt, Jenn M.; Lemay, Matthew A.; Salomon, Anne K.; Martone, Patrick T. (Proceedings of the National Academy of Sciences - PNAS, 2019)
Understanding how trophic dynamics drive variation in biodiversity is essential for predicting the outcomes of trophic downgrading across the world’s ecosystems. However, assessing the biodiversity of morphologically cryptic lineages can be problematic, yet may be crucial to understanding ecological patterns. Shifts in keystone predation that favor increases in herbivore abundance tend to have negative consequences for the biodiversity of primary producers. However, in nearshore ecosystems, coralline algal cover increases when herbivory is intense, suggesting that corallines may uniquely benefit from trophic downgrading. Because many coralline algal species are morphologically cryptic and their diversity has been globally underestimated, increasing the resolution at which we distinguish species could dramatically alter our conclusions about the consequences of trophic dynamics for this group. In this study, we used DNA barcoding to compare the diversity and composition of cryptic coralline algal assemblages at sites that differ in urchin biomass and keystone predation by sea otters. We show that while coralline cover is greater in urchin-dominated sites (or “barrens”), which are subject to intense grazing, coralline assemblages in these urchin barrens are significantly less diverse than in kelp forests and are dominated by only 1 or 2 species. These findings clarify how food web structure relates to coralline community composition and reconcile patterns of total coralline cover with the widely documented pattern that keystone predation promotes biodiversity. Shifts in coralline diversity and distribution associated with transitions from kelp forests to urchin barrens could have ecosystem-level effects that would be missed by ignoring cryptic species’ identities.